Optimasi Pembangunan Tangki Air Tanah dan Sanitasi Menggunakan Metode Program Evaluation and Review Technique (PERT) dan Critical Path Metode (CPM) Agar Efektif Biaya Dan Waktu - Anfaal Al Ghifari, Muhammad; Gustian Djuanda (Forum Kerjasama Pendidikan Tinggi, 2023)
The success or failure of project implementation is often due to the lack of planning of project activities and ineffective control, so that project activities are inefficient, this will result in delays, decreased quality of work, and increased implementation costs. Project management is carried out to manage the project from start to finish. This study aims to determine the optimal time and cost of a ground water tank and sanitation development project at Al-Mulk Hospital, Sukabumi City. The more optimal the time obtained will help the company complete the project at optimal cost. The method used here uses quantitative and data collection techniques through observation, interviews and literature. With the method of data analysis using the Program Evaluation and Review Technique (PERT) and Critical Patch Methode (CPM).